2017
DOI: 10.1007/s11307-017-1150-2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Promotes 2-Deoxy-2-[18F]Fluoro-D-Glucose Uptake in Hepatocellular Carcinoma Cells Through FoxO1-Mediated Downregulation of Glucose-6-Phosphatase

Abstract: We propose that treatment of HCC cells with Met may be a useful strategy for improving the efficacy of [F]FDG as a tracer for PET/CT imaging of HCC tumors in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Mice were treated with normal saline (Con) and MOTS-c (5 mg/kg, per day) for long term (45 days) under room temperature, then mice were allowed to fast six hours and were anesthetized with isoflurane followed by a tail vein injection of 18F-FDG (120 mCi). Thirty mins after the injection of the 18F-FDG, the mice were subjected to PET/CT image test and analysis according to Wang Z. et al [37].…”
Section: Methodsmentioning
confidence: 99%
“…Mice were treated with normal saline (Con) and MOTS-c (5 mg/kg, per day) for long term (45 days) under room temperature, then mice were allowed to fast six hours and were anesthetized with isoflurane followed by a tail vein injection of 18F-FDG (120 mCi). Thirty mins after the injection of the 18F-FDG, the mice were subjected to PET/CT image test and analysis according to Wang Z. et al [37].…”
Section: Methodsmentioning
confidence: 99%
“…For example, 2-DG is an analog of glucose, and it can be catalyzed by HK2 into 2-deoxy-D-glucose-6-phosphate (2-DG-6P), which is different from G-6-P and can noncompetitively inhibit the activity of HK2 [5,35]. When 2-DG was given alone in HCC, it was reported to suppress the growth, metastasis and invasion of HCC cells, and the combination treatment of 2-DG and other chemotherapy drugs, such as sorafenib, 2aminophenoxazine-3-one (Phx-3), and metformin, can also enhance the anticancer effect of them on HCC [179][180][181]. The 3-bromopyruvate (3-BP) is a different type of HK2 inhibitor with the ability to inhibit HK2 activity directly, so as to strongly suppress the glycolysis process.…”
Section: Therapeutic Agents That Target Glycolysismentioning
confidence: 99%
“…It is reported that higher FDG uptake, higher GLUT1 expression and lower G6Pase expression are greater in poorly differentiated HCC than moderately differentiated HCC [11,20]. Among the 12 cases in which extrahepatic metastasis recurred, 1 had a TNR < 1.53.…”
Section: Discussionmentioning
confidence: 99%